The coastal evacuation of Zhangpu County in early Qing: Borders, shifting zones, and social change as seen in forts and fortified villages. Issue 2 (3rd April 2019) - Boyi, Chen
Abstract: Qianhai, the early Qing order that forced people in southeast coast to evacuate the coast to a distance of ten to eighteen miles inland in order to eliminate anti-Qing activities, is an excellent topic through which to examine the formation of the border in Han local society. The development of regional studies during the past 20 years encourages us to both refine our local case studies and map the wider picture. The story of social transformation in Zhangpu County during the Ming-Qing transition provides a perfect case to discuss how the coastal evacuation policy was implemented in local society. It can also promote our understanding of multiple histories. First, the lineage story of the coastal evacuation can be described in greater detail. Even in a single county, there was no standard evacuation distance. Local officials relied on mountainous terrain and existing forts and fortified villages to form a line of defense that determined the scope of the evacuation. Second, the social landscape in the communities of the county demonstrates the rise and decline of local power structures. Many of the most influential and deep-rooted lineages were badly weakened by the time they returned home after the evacuation order was rescinded. On the basis of the ebb and flow of local elites, the Qing state began to regulate households more closely, and state power thus penetrated to the local level. The household registers of Zhangpu were established based on the specific historical context of the county, but the process shared with the rest of the southeastern coastal region a pattern whereby pacification and local Defense shaped state penetration. Even in a supposedly "traditional" Han region, the empire needed to handle the problems of the border and social complexity, just as it did in "non-Han" areas. This illustrates the process of late imperial state formation in practice.